A review of the genus Formicococcus Takahashi 1928 (Hemiptera: Coccomorpha: Pseudococcidae) of China, with description of a new species - Zhang, Jiang-Tao; Wu, San-An (Zootaxa, 2022)
Sixteen species of the genus Formicococcus (Hemiptera: Coccomorpha: Pseudococcidae) are recognized from China. Among them, a new species, F. delonicola Zhang & Wu sp. n., is described and illustrated based on adult females collected from Xishuangbanna, Yunnan, China on Delonix regia (Fabaceae). The new species is similar to Formicococcus latens Williams 2004 in possessing oral collar tubular ducts on the head and in marginal groups on the posterior abdominal segments. However, it differs from the latter in the morphological character states of dorsal setae on abdominal segment VIII, anal ring setae length and tips morphology of cerarian setae. The monotypic genus Anaparaputo Borchsenius 1962 is recognized as a junior synonym of Formicococcus, and Anaparaputo liui Borchsenius 1962 is transferred to Formicococcus as Formicococcus liui (Borchsenius 1962) comb. n. Three species, Paraputo bambusus (Wu 2001), Paraputo eriobotryae (Wang 1985) and Planococcus mumensis Tang 1977 are here restored to Formicococcus, as F. bambusus (Wu 2001) comb. rev., F. eriobotryae Wang 1985 comb. rev. and F. mumensis (Tang 1977) comb. rev. respectively, bringing the number of Formicococcus species found in China to 16. A key to the Palaearctic and Oriental species of Formicococcus is provided.